2016
DOI: 10.1021/acs.energyfuels.6b00254
|View full text |Cite
|
Sign up to set email alerts
|

Self-Accumulation of Uncharged Polyaromatic Surfactants at Crude Oil–Water Interface: A Mesoscopic DPD Study

Abstract: The dissipative particle dynamics (DPD) technique was applied to study the behavior of several uncharged perylene bisimide-based polyaromatic surfactant (PAS) molecules, with the same polyaromatic core but with different terminal functional types (TP, C5Pe, PAP, and PCH) at the crude oil–water interface. We considered the SARA crude oil model with Persian Gulf oil field composition, which includes saturates, 59%; aromatics, 28.5%; resins, 9.7%; and asphaltenes, 2.8% at two temperatures 298 and 363 K. The DPD i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 77 publications
0
29
0
Order By: Relevance
“…There is a correlation between a ij and Florry–Huggins parameter χ ij where a ii is the interaction parameter between the same beads; it can be calculated through the formula given by Groot and Rabone: where k –1 is the dimensionless compressibility factor for water at room temperature and pressure with the value of 15.98; N m is the number of water molecules represented by one DPD water bead (here N m = 3); α = 0.01 ± 0.001; The bead density ρ is set to 3, so we can get a ii = 78. χ ij can be calculated by the BLENDS module of Materials Studio 7.0 software. Combining Monte Carlo simulations and a revised Flory–Huggins model, BLENDS module calculates the χ ij from the blend energy and has been applied in DPD studies. , Table shows the repulsive parameters calculated by COMPASS II , force field at 298 K. The calculation result shows that all a ij between D and polymer beads are smaller than those between W and polymer beads. This indicates that DMF is the good solvent for the polymer while water is nonsolvent.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…There is a correlation between a ij and Florry–Huggins parameter χ ij where a ii is the interaction parameter between the same beads; it can be calculated through the formula given by Groot and Rabone: where k –1 is the dimensionless compressibility factor for water at room temperature and pressure with the value of 15.98; N m is the number of water molecules represented by one DPD water bead (here N m = 3); α = 0.01 ± 0.001; The bead density ρ is set to 3, so we can get a ii = 78. χ ij can be calculated by the BLENDS module of Materials Studio 7.0 software. Combining Monte Carlo simulations and a revised Flory–Huggins model, BLENDS module calculates the χ ij from the blend energy and has been applied in DPD studies. , Table shows the repulsive parameters calculated by COMPASS II , force field at 298 K. The calculation result shows that all a ij between D and polymer beads are smaller than those between W and polymer beads. This indicates that DMF is the good solvent for the polymer while water is nonsolvent.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…There are several reports that the Blend module gives results with a large variation. [65][66][67] In the majority of experimental studies, a higher PCE is reported for c values between 0-3. 60,63 Keeping the lower accuracy of the theoretical method in mind, we selected SMAs with c between 6 and À6.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…It should be noted that Blends module of Materials Studio has been observed to give results with a large variation . To combat this, we utilized post‐processing and data analysis steps developed by the authors which improved the accuracy of the resultant χ‐values significantly.…”
Section: Materials and Simulation Methodsmentioning
confidence: 99%